Mutations in voltage‐gated sodium channels from pyrethroid resistant salmon lice (Lepeophtheirus salmonis). Issue 2 (27th September 2018) - Carmona‐Antoñanzas, Greta; Helgesen, Kari O; Humble, Joseph L; Tschesche, Claudia; Bakke, Marit J; Gamble, Louise; Bekaert, Michaël; Bassett, David I; Horsberg, Tor E; Bron, James E; Sturm, Armin
Abstract: BACKGROUND: Parasitic salmon lice ( Lepeophtheirus salmonis ) cause high economic losses in Atlantic salmon farming. Pyrethroids, which block arthropod voltage‐gated sodium channels ( Na v 1 ), are used for salmon delousing. However, pyrethroid resistance is common in L. salmonis . The present study characterized Na v 1 homologues in L. salmonis in order to identify channel mutations associated to resistance, called kdr (knockdown) mutations. RESULTS: Genome scans identified three L. salmonis Na v 1 homologues, LsNa v 1.1, LsNa v 1.2 and LsNa v 1.3 . Arthropod kdr mutations map to specific Nav 1 regions within domains DI‐III, namely segments S5 and S6 and the linker helix connecting S4 and S5. The above channel regions were amplified by RT‐PCR and sequenced in deltamethrin‐susceptible and deltamethrin‐resistant L. salmonis . While LsNa v 1.1 and LsNa v 1.2 lacked nucleotide polymorphisms showing association to resistance, LsNa v 1.3 showed a non‐synonymous mutation in S5 of DII occurring in deltamethrin‐resistant parasites. The mutation is homologous to a previously described kdr mutation (I936V, numbering according to Musca domestica Vssc1) and was present in two pyrethroid‐resistant L. salmonis strains (allele frequencies of 0.800 and 0.357), but absent in two pyrethroid‐susceptible strains. CONCLUSIONS: The present study indicates that a kdr‐mutation in LsNa V 1.3 may contribute to deltamethrin resistance in L. salmonis . © 2018 Society of Chemical Industry Abstract : Salmon lice were found to possess three voltage‐gated sodium channels (Nav 1). Deltamethrin‐resistant lice showed a missense mutation of Nav 1.3 homologous to a Nav 1 mutation previously linked to pyrethroid‐resistance in insects.